2021
DOI: 10.1177/03635465211008656
|View full text |Cite
|
Sign up to set email alerts
|

Assessment of Skeletal Maturity and Postoperative Growth Disturbance After Anterior Cruciate Ligament Reconstruction in Skeletally Immature Patients: A Systematic Review

Abstract: Background: Growth disturbance is an uncommon but potentially serious complication after anterior cruciate ligament (ACL) reconstruction in skeletally immature patients. Purpose: To describe how the pediatric ACL literature has assessed preoperative skeletal maturity and the amount of growth remaining and to comprehensively review the incidence, reporting, and monitoring of postoperative growth disturbance. Study Design: Systematic review; Level of evidence, 4. Methods: This review included studies reporting o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
16
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 17 publications
(16 citation statements)
references
References 129 publications
0
16
0
Order By: Relevance
“…Although alignment after transphyseal ACLR has been previously evaluated postoperatively in pediatric patients, these studies have been limited by sample size, radiographic field of view (ie, short-leg radiographs only) and/or by referencing postoperative imaging to typical data rather than the patient's presurgical status. 3,5,9,11 This study prospectively compared preoperative with postoperative longleg radiographs and showed that there were no statistically significant changes in mean alignment or longitudinal growth after transphyseal ACLR. However, caution regarding the possibility of growth disturbance should persist given that 7 out of 104 postsurgical patients demonstrated a change in mechanical axis of >10 mm (five patients) or a change in LLD of >10 mm (two patients).…”
Section: The Orthopaedic Journal Of Sports Medicinementioning
confidence: 97%
“…Although alignment after transphyseal ACLR has been previously evaluated postoperatively in pediatric patients, these studies have been limited by sample size, radiographic field of view (ie, short-leg radiographs only) and/or by referencing postoperative imaging to typical data rather than the patient's presurgical status. 3,5,9,11 This study prospectively compared preoperative with postoperative longleg radiographs and showed that there were no statistically significant changes in mean alignment or longitudinal growth after transphyseal ACLR. However, caution regarding the possibility of growth disturbance should persist given that 7 out of 104 postsurgical patients demonstrated a change in mechanical axis of >10 mm (five patients) or a change in LLD of >10 mm (two patients).…”
Section: The Orthopaedic Journal Of Sports Medicinementioning
confidence: 97%
“…The awareness of physeal injury related to the operative treatment of ACL tears in the pediatric population has resulted in several physeal-sparing and physeal-respecting techniques of reconstruction. 6,11 Although some authors criticize these techniques because of its usual ''nonanatomic'' configuration, biomechanical studies have shown otherwise, with a good restoration of kinematic constraint. 7,12 This ITB physeal-sparing technique described by Micheli and Kocher can reduce the risk of physeal damage, maintaining stability and providing excellent functional outcomes, with low revision rates: at a mean follow-up of 5.3 years, from 44 patients, 41 returned to sports involving cutting or pivoting, and the revision rate was at 4.5%.…”
Section: Video Transcriptmentioning
confidence: 99%
“…Additionally, it is a deficiency that can be reduced by using practical strength training and neuromuscular rehabilitation methods. Bilateral landing knee joint loading patterns are significantly impacted by isometric quadriceps femoris strength deficiencies of more than 15% [22,23] . In a recent study, Schmitt and colleagues discovered that people with quadriceps femoris strength impairments had altered landing patterns.…”
Section: Final Postoperative Obstaclesmentioning
confidence: 99%